Tourism and protected areas : motives, actors and processes - Zachrisson, Anna; Sandell, Klas; Fredman, Peter; Eckerberg, Katarina (International Journal of Biodiversity Science & Management, 2006)
Following the paradigm shift in nature conservation policy towards the inclusion of local inhabitants in the planning and management of protected areas, tourism is emphasised as a means to achieve economic development in peripheral areas. Governance issues and the real impacts from tourism on development are thus often under scrutiny. This article focuses on the role of tourism in the political process of designating protected areas. How does the inclusion of the tourism argument affect designation processes? What kind of tourism is being promoted and how can it be conceptualised with regard to human views of the use of nature? An ecostrategic framework is presented to illustrate the essential land-use choices available. Three cases of protected area designation processes are used to address the issue of tourism: the failure of the Kiruna National Park proposal and the successful implementation of the snowmobile regulation area in Funäsdalen and Fulufjället National Park. The analysis shows that while tourism may increase local acceptance of protected areas, the power of this argument also depends on contextual and process factors.